India in the era of China's belt and road initiative how modi responds to Xi - Sigdel, Anil, 1974- (Lexington Books, 2020)
"As the United States wants to see India establish itself as a rival power to China, this book examines the critical questions of how Modi is stepping up his efforts to counter Xi Jinping's Belt and Road Initiative"--